Humor, Eroticism, and Identity: Reading Bali's Lolok Craft through the Lens of Camp and Postmodern Aesthetics - Nofrial, Nofrial; Malik, Kendall (Institut Seni Indonesia Padang Panjang, 2025)
Phallus-shaped craftworks known as lolok, openly sold as souvenirs in Bali, represent a complex cultural phenomenon that blends humor, eroticism, and symbolic local values. This study aims to analyze these objects through the lenses of postmodern aesthetics, relational aesthetics, and camp theory, focusing on how they reflect parody, kitsch, and the commodification of culture. The research employs a literature review and online observation to examine narratives, production, distribution, and public reactions to these crafts across various media platforms. The findings reveal that lolok crafts function not only as tourist merchandise but also as visual artifacts that mediate interactions between local communities and global tourists. These objects blur the boundaries between the sacred and the profane, as well as between local identity and global consumption. They represent a deconstruction of the traditional Hindu-Balinese lingga-yoni symbols, reinterpreted into popular cultural forms. Through the aesthetics of camp, lolok crafts demonstrate how humor and eccentricity can serve as expressive strategies in shaping an adaptive cultural identity. This study concludes that these erotic crafts exemplify a fluid, relational mode of contemporary craft practice rooted in the sociocultural dynamics of tourism.